Chronic Diseases: Chronic Diseases and Development 2 Health, agricultural, and economic effects of adoption of healthy diet recommendations - Lock, Karen; Smith, Richard D.; Dangour, Alan D.; Brown, Marcus Keogh; Pigatto, Gessuir [UNESP]; Hawkes, Corinna; Fisberg, Regina Mara; Chalabi, Zaid (Elsevier B.V., 2010)
Transition to diets that are high in saturated fat and sugar has caused a global public health concern as the pattern of food consumption is a mayor modifiable risk factor for chronic non-communicable diseases Although agri food systems are intimately associated with this transition, agriculture and health sectors are largely disconnected in their priorities policy, and analysis with neither side considering the complex inter relation between agri trade patterns of food consumption health, and development We show the importance of connection of these perspectives through estimation of the effect of adopting a healthy diet on population health, agricultural production trade the economy and livelihoods, with a computable general equilibrium approach on the basis of case studies from the UK and Brazil we suggest that benefits of a healthy diet policy will vary substantially between different populations, not only because of population dietary intake but also because of agricultural production trade and other economic factors